Positive Association Between Self-Reported Fatty Food Consumption and Factor VII Coagulant Activity, a Risk Factor for Coronary Heart Disease, in 4246 Middle-Aged Men - Connelly, J B; Roderick, P J; Cooper, J A; Meade, T W; Miller, G J (Thrombosis and Haemostasis, 1993)
Raised levels of factor VII coagulant activity (VIIC) have been reported to increase the incidence of CHD. Preliminary evidence from observational and experimental studies suggests that dietary fat intake is positively associated with VIIC. We explored this further in 4,246 men aged 45–69, who were found to be free of major CHD when screened for a primary prevention trial of antithrombotic medication. All men were asked about their consumption of fatty foods and changes in consumption in the last month.In the 9% of men who reported avoidance of fatty foods in the month before interview, age adjusted VIIC was 7.8% of standard (95% CI 5.1–10.6%) lower than in the remainder. Serum cholesterol and body mass index (BMI) were also significantly lower. The extent to which fat consumed in the past month had deviated from usual intake was significantly and positively related with VIIC, serum cholesterol and BMI. Thus, the VIIC difference between those eating much less fatty food than usual and those eating much more than usual was 11% of standard, with those eating their usual amount having an intermediate level.This study adds to the evidence that dietary fat intake influences VIIC and coagulability. The effect is rapid, so that much of the benefit of dietary fat reduction on thrombogenic risk in CHD is likely to occur within a short time. Thus, the results reinforce the value of a low fat diet, even in individuals with advanced atheroma, in whom dietary intervention has sometimes been considered unlikely to be effective.